PENERAPAN MODEL KEPEMIMPINAN MENURUT ROBERT K. GREENLEAF DALAM KEPEMIMPINAN SEKOLAH-SEKOLAH KATOLIK DI KOTA MADIUN - Ignatius Rio Praseno; Agustinus Supriyadi (Bahasa Indonesia, 2022)
Today, Catholic schools are called to serve and educate human beings to become integral persons, and to achieve their fulfillment in Christ. Therefore, the servant leadership model should be applied to the leadership of Catholic schools. The reason is that servant leadership is a leadership model taught by Jesus Himself. This paper uses the theory of servant leadership according to Robert K. Greenleaf. The problems: Do the leaders of Catholic schools understand the concept of servant leadership? How is the model of servant leadership applied in Catholic schools? This study aims to answer this problem. This study uses a qualitative research method with the interview method. The results showed that all the leaders of Catholic schools understood the basic concept of servant leadership. The servant leadership model has been well applied in various activities, policies, programs, and attitudes displayed by the leaders of Catholic schools. The implementation is based on ten characteristics of servant leadership.